Risks That Facing Tourism And The Managing Methods In The contemporary Challenges Theoretical study - سالم, سالم حميد (Journal of Economics and Administrative Sciences, 2017)
Tourist business organizations face a challenging and the risks dynamic environment reflected its impact on the community and generate extra under pressure in the responsibilities and burdens of exceptional and affected much of factors, accidents and risks as a result of the actions and attitudes of disasters variety may exceed the geography of States border, which requires the absorption of risks facing the tourism and how to manage and deal with them scientific and reasonable grounds for the diagnosis and treatment of risk and how to reduce the aggravation and the different kinds.As risks affecting the most important and vital to organizations as a tourist aspects of the market share and styles tourist target segments as well as directing traffic for the purposes of tourism and travel.This requires knowledge of the types of hazards and assess the size and development of strategies to manage them through to avoid and reduce the negative effects and consequences on the reality of tourist traffic. And it highlights the importance of research of the importance of the subject of risk management in a challenging and changing environment reflection  in the size and future of tourist activity as well as to identify the types of risks in the tourist business and ways to address them in order to prevent aggravation، The ultimate goal is to search to identify the risks facing the business and reflected in the nature of the tourist business, methods, and methods of treatment according to the proposed tables in search facility types.The researcher followed a method descriptive analysis in dealing with the subject of research of the concepts and terminology of risk management and attempt to build scale to identify the possible risks in the tourist environment with reference to the extent appropriate to describe the practical cases represent the reality of these factors in tourism patterns prevailing in the Middle East.The researcher's conclusions, including: the existence of significant challenges for risk tourism and in many forms as businesses theft of relics, bombings and vandalism of the parks and tourist cities and weighed heavily on tourist traffic in the Middle east .add for the emergence of anti-religious movements for business tourism, and the emergence of climate change, a new and unfamiliar delimiters constitute inbuilt vulnerabilities.The researcher recommended that an emphasis on continuous development to cope with the risks of all kinds and levels, and the need to pay attention and focus on the areas of risk to the stage of early warning in order to detect them and limit their consequences.